Preface (Global Governance of Low Earth Orbit Satellites, 2025)
This book is the culmination of our, the co-editors of this volume, project on the Global Governance of Low Earth Orbit Satellite Broadband, generously funded by the Internet Society Foundation as part of its transformative Decolonizing the Internet program. Since 2023, the project has embarked on a pivotal second phase, focusing on the crucial themes of “Trust and Data Governance”.